"Doing God" in Number 10: British Prime Ministers, Religion, and Political Rhetoric. Issue 1 (23rd January 2015) - Crines, Andrew S.; Theakston, Kevin
Abstract: This article analyses British prime ministers' use of religious language and their own religious beliefs in their political rhetoric. This is used to justify policy, support their ideological positions, present a public persona, and cultivate their personal ethical appeal and credibility as values-driven political leaders. The focus is on the use and the nature of the religious arguments of Margaret Thatcher, Tony Blair, Gordon Brown and David Cameron. As political leaders, British prime ministers are aware of the need to modify and tailor their language in response to changing audiences and contexts. "Doing God" is a difficult and risky rhetorical strategy for British prime ministers but it increasingly has the potential to yield political benefits.